Causality analysis in corporate social responsibility and financial performance: Evidence from Indonesia - Satria, Bagas Ardhi Yoga; Gunarsih, Tri (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
The causality and bi-causality between corporate social responsibility and firm financial success are examined in this study. Companies listed on the Indonesia Stock Exchange for the years 2018 through 2021 make up the study's population. The sampling method utilized is the purposive sampling method, which involves selecting samples based on criteria. 62 companies made up the sample. The Granger’s causality test is the causality test that is employed. The findings revealed that: 1) Corporate social responsibility has a positive impact on financial performance as measured by price to book value and earnings per share. 2) Price to book value and earnings per share, which are financial performance indicators, have a positive impact on corporate social responsibility. 3) There is a correlation between corporate social responsibility and financial performance, as measured by price to book value and earnings per share, which is bi-causal (two-way causality) and positive in direction.